The Effect of Using Song Vocabulary to Students’ Retention - Rifka Nurin Nafisah; Albadri Albadri; Musdalifah Musdalifah (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2026)
This study determines the effect of using song vocabulary to students’ retention. This research was conducted at the grade Intermediate in Syu’batul Lugha Al-Khairiyah, Ma’hadul Qur’an, Sukorejo, Situbondo. This research used a quantitative method by using Pre-Experimental research type one group pretest posttest design. This research used saturated sampling technique, which a whole of population which consists 19 students are sample. The instrument data collection used test. Data analysis technique using analysis of t-test by paired sample t-test. It was gotten t0 = (-19.396) > tt = (2,861) with sig. (2-tailed) value was 0,000. So, it meant that H0 is refused and Ha is accepted.